Distinguishing analgesic drugs from non-analgesic drugs based on brain activation in macaques with oxaliplatin-induced neuropathic pain. (1st May 2019) - Shidahara, Yuka; Natsume, Takahiro; Awaga, Yūji; Ogawa, Shin'ya; Yamoto, Kurumi; Okamoto, Shinichi; Hama, Aldric; Hayashi, Ikuo; Takamatsu, Hiroyuki; Magata, Yasuhiro
Abstract: The antineoplastic agent oxaliplatin is a first-line treatment for colorectal cancer. However, neuropathic pain, characterized by hypersensitivity to cold, emerges soon after treatment. In severe instances, dose reduction or curtailing treatment may be necessary. While a number of potential treatments for oxaliplatin-induced neuropathic pain have been proposed based on preclinical findings, few have demonstrated efficacy in randomized, placebo-controlled clinical studies. This failure could be related, in part, to the use of rodents as the primary preclinical species, as there are a number of distinctions in pain-related mechanisms between rodents and humans. Also, an indicator of preclinical pharmacological efficacy less subjective than behavioral endpoints that is translatable to clinical usage is lacking. Three days after oxaliplatin treatment in Macaca fascicularis, a significantly reduced response latency to cold (10 °C) water was observed, indicating cold hypersensitivity. Cold-evoked bilateral activation of the secondary somatosensory (SII) and insular (Ins) cortex was observed with functional magnetic resonance imaging. Duloxetine alleviated cold hypersensitivity and significantly attenuated activation in both SII and Ins. By contrast, neither clinically used analgesics pregabalin nor tramadol affected cold hypersensitivity and cold-evoked activation of SII and Ins. The current findings suggest that suppressing SII and Ins activation leads to antinociception, and, therefore, could be used as a non-behavioral indicator of analgesic efficacy in patients with oxaliplatin-induced neuropathic pain. Highlights: Oxaliplatin-treated macaques demonstrate robust cold hypersensitivity. Cold activates insula and secondary somatosensory cortex. Duloxetine but not pregabalin and tramadol are antinociceptive. Duloxetine blocks cold-evoked brain activation but pregabalin and tramadol do not. Findings suggest brain activation delineates analgesic from nonanalgesic drugs.